Internalisasi nilai karakter global dalam pembelajaran pendidikan kewarganegaraan di sekolah dasar - Chintya Eria Suryawati; Adilla Putri Febriani; Salsabila Intan Iswidiarmi; Suhadidilla Putri Febriani; Sifana Aradesita (Universitas PGRI Madiun, 2026)
Globalization presents increasingly complex challenges for elementary school students in maintaining national identity while responding to global developments. Citizenship Education plays a strategic role in strengthening global character values through meaningful, contextual, and reflective learning processes. This study aims to analyze the internalization of global character values in Citizenship Education learning at the elementary school level. This research employed a qualitative approach based on the synthesis of findings from various relevant studies. Data were collected through literature review and analyzed using content analysis techniques by identifying, categorizing, and interpreting patterns related to global responsibility, tolerance, social awareness, and national identity. The findings reveal that Citizenship Education learning contributes significantly to the development of students’ global character through the integration of global issues, contextual learning activities, and teacher role modeling. The synthesis indicates that students tend to demonstrate positive attitudes toward tolerance and social awareness, while global responsibility remains an aspect that requires continuous reinforcement. These findings highlight the importance of innovative learning strategies, contextual educational resources, and sustainable character education to develop globally competent students while maintaining national values.